تأثير برامج الخدمة الاجتماعية على مواجهة التفكك الأسري: دراسة تطبيقية بكلية التربية، زوارة (Comprehensive Journal of Science, 2025)
This study aimed to explore the relationship between family breakdown and family problems, as well as to examine the role of social work programs in addressing family breakdown and supporting families in performing their roles effectively. The study adopted a descriptive-analytical approach, focusing on examining current phenomena, analyzing influencing factors, and interpreting results within their social and academic context.The study population consisted of students from the Faculty of Education at Zuwara University. A random sample of 70 questionnaires was selected, and 60 complete questionnaires were analyzed to ensure accuracy. A survey was used to measure socialization, family relationships, and the role of social work programs in promoting family cohesion.The study employed frequency distribution and percentages to analyze the data. The results indicated that family breakdown is influenced by factors such as religious values, social bonds, economic conditions, and modern cultural changes. Families partially recognize the preventive role of social work, but there is a knowledge gap regarding the tasks of social workers.The study recommended increasing public awareness of social work, activating family guidance programs, providing material and psychological support to families, developing psychological support programs for children, expanding social services, and integrating family education and social and religious values into school curricula to strengthen family cohesion and prevent breakdown.